Operationalising the Trade Policy Unit Ministry of Investment and Trade, Belize - Odle, Stanley C. ([CARICOM Secretariat] [Georgetown]GY, 2000)
Focuses primarily on the information technology resources, and the human skills that are required to endow the Belize Trade Policy Unit with the means of bringing about improvement in Belize's trade decision-making.